Antimicrobial Resistance: A Situational Analysis in the Deido Health District, Douala, Cameroon - Njumkeng Charles; T. AMIN Elvis; Zofou Denis; K. T. Akoachere Jane-Francis; A. Njukeng Patrick (Journal of Preventive Medicine And Care, 2021)
Background The rapid and ongoing spread of antimicrobial-resistant organisms threatens the ability to successfully prevent, control, or treat a growing number of infectious diseases in developed and developing countries. This study was designed to convey more insight on the profile of antimicrobial resistance and the capacity of laboratories conducting antimicrobial susceptibility testing in Cameroon. Methods A multicentre cross-sectional study was conducted from October 2019 to March 2020 in the Deido Health District. Laboratories that carry out culture and sensitivity testing within the Deido Health District were identified and assessed to determine their capacity as well as the quality of results from microbiological investigations. Information on antimicrobial susceptibility of various isolates was collected using tablet phones in which the study questionnaires had been incorporated. Results Gaps identified in antimicrobial susceptibility testing that cut across laboratories included; insufficient standard operating procedures, inadequate records on personnel training and competency assessment, lack of safety equipment such as biosafety cabinet, stock out and non-participation in external quality assurance program. The turnaround time for antimicrobial susceptibility testing ranged from 3 – 7 days. Out of the 1797 samples cultured, 437(24.3%) had at least one isolate. A total of 15 different isolates were identified with Candida albicans being the most frequent 178 (40.7%), followed by Escherichia coli 80(18.3%). Among the 15 classes of antimicrobial drugs used in this study, the overall resistance of the isolates showed that five classes had class median resistance above 40% (Cephalosporins, Penicillins, Beta-lactam, Macrolides, and Polyenes). Conclusion This study has shown the need to develop a coordinated national approach to fight antimicrobial resistance. Scaling-up of antimicrobial susceptibility testing will, therefore, require strengthening the microbiology units of laboratory systems as well as ensuring the use of laboratory data for decision making.
Keywords: Gram-negative bacteria